The tie is old hat - Abd Razak, Dzulkifli (2006)
WHAT’S in a tie. Plenty, going by recent events. First, the Canadian Parliament. Some years ago, I watched a televised Canadian session where a member of the House was not allowed to speak because he wore a turtleneck sweater and did not have a tie on. The quick thinking member borrowed a tie from his colleague and fixed it over the turtleneck and was allowed to speak. This Canadian incident illustrated the point that a piece of cloth tied around the neck is accorded such importance. There was a "Canadian" affair in the Malaysian Parliament recently involving a Minister. Although not as dramatic as the Canadian incident, the implication was similar.